Measurement of the CP asymmetry in B0→K*0μ+μ− decays - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Dordei, Francesca; Eisele, Franz; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
A measurement of the CP asymmetry in B0→K*0μ+μ− decays is presented, based on 1.0 fb−1 of pp collision data recorded by the LHCb experiment during 2011. The measurement is performed in six bins of invariant mass squared of the μ+μ− pair, excluding the J/ψ and ψ(2S) resonance regions. Production and detection asymmetries are removed using the B0→J/ψK*0 decay as a control mode. The integrated CP asymmetry is found to be −0.072±0.040(stat)±0.005(syst), consistent with the standard model.
Im Titel sind "0", "*0", "+" und "-" hochgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, F. Dordei, F. Eisele, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 576
Gesehen am 23.03.2021